Peran Active Learning Dalam Pembentukan Karakter Peserta Didik di MTs Negeri 8 Ngawi - Sumarno Sumarno; Nuril Afiati (Al-Lubab : Jurnal Penelitian Pendidikan dan Keagamaan Islam, 2021)
The purpose of this study is to find out how the implementation of active learning in shaping the character of MTsN 8 Ngawi students. The method in this study is qualitative field research that is descriptive. The data collection techniques are conducted with interviews, observations, and documentation. The analysis technique goes through the stages of data reduction, data presentation and conclusion drawing. The results of this study can be described as follows; 1. The implementation of active learning conducted at MTsN 8 Ngawi has been very good in its application so that many students pay attention when teaching and learning activities take place. 2. The character of the students in MTsN 8 Ngawi in accordance with Islamic rules can support the excellence of the spiritual intelligence of learners, the personality of good learners, the achievement of students who improve. 3. The role of active learning in the formation of the character of MTsN 8 Ngawi learners is very good and improves the quality of the character of the learners, with the active learning of students more active, responsive and responsible.